Geometry engineering of tunneling transistors in transition metal dichalcogenide nanoribbon heterojunctions - Ye Jiang; Minjiang Dan; Shuaiwei Fan; Gongwei Hu; Fobao Huang; Wei-Yang Wang; Qiao Chen (Communications Physics)
Abstract Graphene nanoribbon heterojunctions are promising one-dimensional materials for quantum electronics due to their tunable bandgap and sizable quantum confinement. However, their band alignment is significantly influenced by dimensional fluctuations, impeding the development of stable and reliable devices. Here, we engineer geometry edges of transition metal dichalcogenide (TMD) nanoribbons to design versatile nanoribbon heterojunctions by combining metallic zigzag and semiconducting armchair edges. T- and H-shaped nanoribbons exhibit robust edge-state transport for tunneling and resonant tunneling, respectively. The quantized subbands confined within H-shaped nanoribbon are modulated by zigzag edges. In contrast, T-shaped configuration shows different tunneling for electrons and holes, which are tunable via armchair edges. Moreover, the device characteristics suggest that tunneling transistors display moderate current dependence on the barrier width, while resonant tunneling transistors exhibit negative differential resistance with peak-valley ratio improved by lengthening armchair edge. This study proposes using geometry edge as a degree of freedom to engineer two-dimensional material nanoribbon heterojunctions, with broad potential for quantum electronic and optoelectronic applications.